Use of Modern molecular Genetic Methods to Study Genetic Diversity of Hepatitis B Strains on the Territory of Khabarovsk City - V. O. Kotova; L. A. Balahotseva; E. Yu. Sapega; O. E. Trotsenko; T. A. Zaitseva (Эпидемиология и вакцинопрофилактика, 2016)
A molecular genetic analysis of 23 samples of blood serum/plasma taken from patients with chronic hepatitis B was performed. The dominant genotype among studied group was genotype D (71.4%); the rate of genotype A and genotype C was 10.7 and 17.9%, respectively.